Characterization of Cd36_03230p, a putative vanillin dehydrogenase from Candida dubliniensis. Issue 102 (20th October 2016) - Datta, Suprama; Annapure, Uday S.; Timson, David J.
Abstract : Despite its annotation as such, Cd36_03230p is not a vanillin dehydrogenase. Abstract : A coding sequence ( CD36-03230 ) from the yeast Candida dubliniensis had been previously annotated as a vanillin dehydrogenase (VDH). The corresponding protein (CD36-03230p) was recombinantly expressed in Escherichia coli and analysed. The protein is most likely a tetramer in solution as judged by crosslinking and gel filtration experiments. CD36-03230p is an active aldehyde dehydrogenase favouring cyclic and aromatic substrates. Positive cooperativity and substrate inhibition were observed with some substrates. The redox cofactor NADP + and substrates affected the thermal stability of the protein. Interestingly, the enzyme had no detectable activity with vanillin suggesting that the annotation is incorrect. It has been previously hypothesized that a methionine residue at a key position in the active site of yeast aldehyde dehydrogenases sterically hinders cyclic substrates and restricts specificity to aliphatic aldehydes. Molecular modeling of CD36-03230p demonstrates that it has an isoleucine residue (Ile-156) at this position, further strengthening this hypothesis.